Notes on Branchiosyllis uncinigera (Hartmann-Schröder, 1960) new to the Mediterranean - Harlock, R.; Laubier, L. (Israel Journal of Zoology, 1966)
The species is redescribed from three specimens from Israel and a paratype of Trypanosyllis uncinigera Hartmann-Schröder, 1960. Due to its claw-bristles and lack of trepan, it has been transferred from Trypanosyllis to Branchiosyllis, despite having no branchiae. The species and genus are new for the Mediterranean.
Kristian Fauchald's Polychaeta DB